Evolutionary genetics analysis for complete plastomes and diversification rate estimation of Deutzia and Philadelphus in tribe Philadelpheae (Hydrangeaceae) - Zhilong Huang; Mimi Li; Chuxin Liang; Qin Fan; Wenya Yu; Shu’an Wang; Meixiu Lin; Pan Li; Rongjing Zhang; Wei Gong (BMC Plant Biology)
Abstract Background Tribe Philadelpheae, belonging to the Hydrangeaceae family, is mainly composed of two genera Deutzia and Philadelphus, both of which demonstrate disjunct distribution in Eastern Asia, North America to Central America, or Southeastern Europe. So far, the phylogenetic relationship and evolutionary history have not yet been well resolved. Results In the current study, we report the complete plastomes of Deutzia and Philadelphus species. Comparative analysis of gene content, structure variation, simple sequence repeats (SSRs) distribution, pseudogenes, as well nucleotide diversity were investigated. The structures of these plastomes of both Deutzia and Philadelphus were generally conserved without any expansion/contraction of the IR regions. Phylogenetic analysis based on the complete plastomes was conducted, which strongly supported the monophyly of each genus. Remarkable associations were detected between species and their geographic distributions, indicating regional geographic specificity. Diversification rate estimation showed relatively higher diversification rate occurring in Eastern Asia than that of Europe and North America. Conclusions The plastomic data provided new insights into the phylogenetic relationships and enhanced the understanding of the evolutionary history of tribe Philadelpheae, which will provide more genomic information for further phylogenomic analyses, speciation or biogeographic inference of tribe Philadelpheae or the Hydrangeaceae family.